Is change in blood pressure a biomarker of pazopanib and sunitinib efficacy in advanced/metastatic renal cell carcinoma?. (January 2016) - Goldstein, David; Rosenberg, Jonathan E.; Figlin, Robert A.; Townsend, Raymond R.; McCann, Lauren; Carpenter, Christopher; Pandite, Lini
Abstract: Aim: Pazopanib, an oral antiangiogenic agent, is associated with improved outcomes in patients with metastatic renal cell carcinoma. In this retrospective analysis, we explore hypertension, an on-target adverse event, as a predictive marker. Methods: Data from the pazopanib arm of the phase III COMPARZ trial (NCT00720941) comprised the test set. Pooled data from phase II (NCT00244764) and III (NCT00334282) pazopanib trials comprised the validation set. Data from the sunitinib arm of COMPARZ were analysed separately. Measures of efficacy were response rate, progression-free survival (PFS), and overall survival (OS). Mean arterial blood pressure (MAP) was the primary metric, and systolic hypertension (S-HTN) and diastolic hypertension (D-HTN) were secondary metrics; 4- and 12-week landmark analyses were performed. Results: Analyses revealed no significant associations at the landmarks between response and MAP. We observed a trend towards improved PFS with S-HTN at week 4 (hazard ratio [HR] = 0.79, P  = 0.060) and week 12 (HR = 0.75, P  = 0.073) among pazopanib-treated patients in COMPARZ. This trend was not confirmed at week 12 in the validation set or in sunitinib-treated patients. In the test set, there was a trend towards increased OS in patients with S-HTN by week 4 (HR = 0.76, P  = 0.062) and with D-HTN by week 4 (HR = 0.71, P  = 0.016) but not by week 12. No significant differences in OS were observed in sunitinib-treated patients for S-HTN or D-HTN. Conclusion: Neither hypertension nor any blood pressure elevation above baseline was associated with efficacy outcomes of pazopanib or sunitinib. Accordingly, management of tyrosine kinase inhibitor-induced hypertension is unlikely to compromise outcome. Highlights: Hypertension is a commonly observed adverse event with angiogenesis inhibitors. We explore hypertension as a predictive marker with pazopanib and sunitinib in renal cell carcinoma. In data from three trials, hypertension was not associated with efficacy outcomes.